Cardiorespiratory Fitness of Pencak Silat Extracurricular Participants at SMK Angkasa - Herman, Andika Raflesia; Angkawidjaja, Lucky; Carsiwan, Carsiwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to determine cardiorespiratory fitness in students who take part in the Pencak silat extracurricular at SMK 1 Angkasa. This type of research uses a non-experimental category with descriptive observational research methods. The population of this study consisted of 10 students participating in the Pencak Silat extracurricular with an age range of 16-18. This research used an instrument in the form of the 6MWT (6 minutes walking test). The research results prove that the average expected distance that can be covered by SMK 1 Angkasa Pencak Silat participants is around 769m, while the research results prove that the average distance covered by students is around 461m. The next data result for the expected percentage is 80.09% while the research results prove that the average percentage of SMK 1 Angkasa Pencak Silat participants is 60.01%.